KONSEP PSIKOLOGI ISLAM DALAM SASTRA SUFI - M.A. Subandi (Millah: Journal of Religious Studies, 2010)
The article aims to elaborate the concepts of general psychology and particularly of Islamic psychology in the literary works of sufistic community, mainly on poems. There are three fields of psychology studied in this article, i.e. psychology of development, psychology of personality and psychoteraphy. The poems as sources of study are not only from Middle East works, but also from Indonesia. Islamic psychology which has been developed by Muslim psychologists recently is an alternative psychology against Western (modern) psychology. As a reference of development, the concept and theory of Islamic psychology come not only from al Qur’an and Hadist, but also from various philosophers, Ulemas, and Sufi’s figures.